Implementation of HOTS-Oriented Short Story Learning Assessment from a Feminist Perspective - Sumiyati Sumiyati; Vismaya S. Damayanti; S. Sumiyadi Sumiyadi; H. Halimah Halimah; Rosita Rahma (Journal of General Education and Humanities, 2026)
The development of Higher Order Thinking Skills (HOTS) has become a central objective in contemporary language and literature education, particularly in short story learning, which requires students to interpret meanings, evaluate values, and reflect on social realities represented in literary texts. However, assessment practices in literature learning often remain focused on lower-order cognitive skills and have not fully accommodated critical perspectives that encourage deeper analysis. This study aims to describe the implementation of HOTS-oriented short story assessment in Indonesian language learning by integrating a feminist perspective as a framework for critical literary analysis. The research employed a qualitative descriptive approach conducted in a vocational high school context. Data were collected through document analysis, classroom observation, and the examination of students’ assignments related to short story learning activities. The findings indicate that HOTS-based assessment tasks, such as analytical questions, evaluative responses, and reflective writing, encourage students to develop interpretative, critical, and reflective thinking when engaging with literary texts. Students were able to analyze narrative conflicts, evaluate gender relations represented in the stories, and connect textual meanings with broader social experiences. The integration of a feminist perspective in literary assessment adds a dimension that promotes critical awareness of social and gender issues while strengthening higher-order thinking processes. This study contributes to the development of literary learning assessment by demonstrating that integrating HOTS and feminist perspectives can support more contextual, critical, and meaningful practices of literature learning.